PENGARUH PENGGUNAAN ASI PADA PERAWATAN LUKA PERINIEM DENGAN LAMA WAKTU PENYEMBUHAN LUKA PERINIUM - Mutmainnah, Annisa Ul; Noorbaya, Siti (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
Childbirth is a natural process, but sometimes labor can also cause birth canaltrauma, especially in the aluminum region, this trauma can be injuries to the periniumarea, the cause can be intentional biases such as episiotomy or unintentional actions such as spontaneous tears in the process of removing the baby. Injury to the perineum if not treated properly can cause postpartum infection because the wound area will be a medium for developing germs. The purpose of this study was to analyze the effect of the use of breast milk in the treatment of periniem wounds with the duration of perinium wound healing at the Ramlah Parjib Clinic in Samarinda. The method used in this study was Posttest Only Control Group Desigen research subjects were postpartum motherswith a sample of 60 respondents taken by random sampling and grouped based on treatment using ASI. Data analysis using ANOVA test. The results showed that the use of ASI had a significant effect on the treatment of periniem wounds with a healing time seen from the P value of 0,000. Conclusion: Periniuem wound care techniques are factors that influence the duration of perinieum wound healing